1987
DOI: 10.1203/00006450-198706000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of Ventilation and CO2 Production during Exercise in Children

Abstract: ABSTRACT. The purpose of this study was t o determine how ventilation (VE) and C 0 2 production (VC03 in response to exercise change during the growth process in children and teenagers. Dynamic gas exchange responses were measured in two types of studies: 1) 128 healthy children ranging in age from 6 to 18 yr performed progressive exercise tests ("ramp" type protocol) for measurement of,the slope of the relationship between VE and VCOZ-AVE/AVCOZ; and 2) the response characteristics of VE and VC02 in the transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
75
1
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 17 publications
12
75
1
3
Order By: Relevance
“…5 A progressive exercise study was carried out using a protocol developed by Cooper and colleagues, as reported previously. 6 Of the patients enrolled in this segment of the study, only 20 completed both pre-and postoperative exercise studies. Recognizing from the start the difficulties in obtaining consistency in multicenter exercise testing, the CRC for the study traveled to each center to make every effort to standardize data collection.…”
Section: Cohort Management and Retentionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 A progressive exercise study was carried out using a protocol developed by Cooper and colleagues, as reported previously. 6 Of the patients enrolled in this segment of the study, only 20 completed both pre-and postoperative exercise studies. Recognizing from the start the difficulties in obtaining consistency in multicenter exercise testing, the CRC for the study traveled to each center to make every effort to standardize data collection.…”
Section: Cohort Management and Retentionmentioning
confidence: 99%
“…In the absence of a change in chemoreceptor set point for Pa CO 2 , the most likely explanation for increased ventilation is increased dead-space ventilation. 6 Because differences in arteriovenous difference for oxygen are likely to be small, changes in the slope of DV O 2 /DHR (change in O 2 consumption/change in heart rate) are likely to reflect changes in stroke volume. 8 These values were examined because the slopes can be measured throughout the progressive exercise test and they do not depend solely on maximum or peak values and, therefore, were expected to be more robust across studies from multiple sites or centers.…”
Section: Cohort Management and Retentionmentioning
confidence: 99%
“…Ohuchi et al 31 demonstrated that the magnitude and change in end-tidal to arterial carbon dioxide tension difference P(ET-a)DCO 2 during graded exercise were smaller, with children showing lower values than adults in both at anaerobic threshold and peak of exercise. We postulate that this finding may be explained by a lower ventilatory efficiency 4,13,[25][26][27] and a lower glycolytic capacity during exercise in children than adults [1][2][3][6][7][8][9] .…”
Section: Figure 1 -A) Rr -Respiratory Rate; B) Ve -Pulmonary Ventilatmentioning
confidence: 84%
“…Children are not adults in miniature; they grow up, and as such, physiologic and metabolic responses to exercise vary accordingly as they progress through childhood and adolescence [1][2][3][4][5] . In relation to the bioenergetic profile, a large number of studies 1,3,[6][7][8] suggested that children have lower anaerobic or glycolytic capacity to produce adenosine 5-triphosphate (ATP) during exercise.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation